KELELAWAR SOPPENG SEBAGAI WARISAN BUDAYA LOKAL DAN DAYA TARIK WISATA KABUPATEN SOPPENG - Ramadhany Arsham, Luthfiyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Bats in Soppeng Regency represent a unique phenomenon of significant historical, cultural and ecological value, and form a distinctive local identity. Their presence in the centre of Watansoppeng Town is preserved through local beliefs and supported by local government policies, thereby ensuring their conservation as a cultural heritage amidst urban development. This study aims to examine the role of Soppeng bats as a cultural heritage asset and a potential tourist attraction in supporting regional tourism development.This study employs a qualitative descriptive approach through a literature review of relevant scientific sources. The findings indicate that the bats possess strong historical significance, closely linked to local myths and traditional agreements between the king and the community, and influence urban spatial planning due to habitat conservation efforts. Furthermore, the bats serve as a unique tourist attraction capable of boosting visitor interest, particularly if supported by management based on local wisdom and effective digital promotion strategies.